Mechanisms linking blue light exposure, circadian misalignment and metabolic dysregulation in adolescents - Staszko, Natalia; Bała, Kamila; Biskup, Alicja; Smagowska, Julia; Zbroniec, Jakub; Bukowska, Małgorzata (Quality in Sport, 2026)
Sleep disturbances and circadian rhythm disruption in children and adolescents represent a growing public health concern and are increasingly linked to the development of metabolic disorders. Adolescence is characterized by a physiological delay in chronotype which, when combined with social pressures and increasing evening exposure to blue light, promotes desynchronization of the biological clock and the phenomenon of social jetlag. The aim of this paper was to discuss the mechanisms through which circadian rhythm disturbances and sleep deprivation affect glucose metabolism and the risk of insulin resistance in adolescents. Particular attention is given to the role of melatonin and its receptors, activation of the hypothalamic-pituitary-adrenal axis, chronic low-grade inflammation, dysregulation of clock gene expression, alterations in the gut-brain axis, reduced adiponectin levels, and decreased non-exercise activity thermogenesis (NEAT). The significance of chrononutrition and peripheral clock misalignment in the pathogenesis of metabolic jetlag is also addressed. The available evidence indicates that sleep and circadian rhythm disturbances, exacerbated by exposure to blue light, constitute an important and potentially modifiable risk factor for the development of insulin resistance, overweight and obesity during childhood and adolescence.